OMUL CA ȘI CONDIȚIE DIVINO-UMANĂ. REPERUL CREȘTIN PENTRU SOCIETATEA AFLATĂ ÎN DEPRESIE AXIOLOGICĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Man as a Divine-Human Condition. The Christian Benchmark for a Society in a Axiological DepressionI wanted to write a study defining the human condition in this state of horizontal crisis. Unfortunately, human society is living a consumerist horizontality without any tendency towards an excelsior of his own life. We have lived a permanent history in which the most important thing and moment was the fight or the war. Likewise we have lived a permanent history in which the most important thing and moment was the fight or the war. There are a few steps in which we manage to recover that divine state we have lost. First of all the idea that we do not die, but only enter into eternity. Secondly we are ecclesial people and creation is a cathedral in which we are the priests of the cosmic liturgy. In the end, we are eucharistic and doxological beings who shed divine glory over creation. Only in this way can the human condition recover itself.